2007
DOI: 10.5387/fms.53.109
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Incidentally Found Cancers Detected by 18f-FDG Positron Emission Tomography/Ct at One Examination

Abstract: During the initial 8 months period of lBF-FDG PET/CT examination in our institution eleven cases of double cancers were detected. Eight cases were simultaneous second cancers and 3 cases are consecutive cancers. All cases are clinical ones and were referred from both outside hospitals and our own hospital. lBF-FDG PET/CT examination were utilized either to determine the extent of tumor or to stage the cancer or to detect recurrent tumors during the follow-up period.During the 8-months period 964 cases were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…These studies were than narrowed down to 63 studies. Thirty-one studies 1,5,14-42 were included for final analysis ( Figure 1 ), and 32 studies 43-74 were excluded as they did not meet the inclusion criteria. All the studies identified were retrospective, noncomparative cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were than narrowed down to 63 studies. Thirty-one studies 1,5,14-42 were included for final analysis ( Figure 1 ), and 32 studies 43-74 were excluded as they did not meet the inclusion criteria. All the studies identified were retrospective, noncomparative cohort studies.…”
Section: Resultsmentioning
confidence: 99%